Strategi Penerapan Pelayanan Prima Pada Jamun Medical Indonesian - Wardana; Lia Lestari, Dewi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research was conducted to find out how excellent service is provided to consumers based on the experience of consumers who visit PT Jamun Medical Indonesian Majalaya branch, Bandung Regency. In providing services, it is important to do well without prioritizing who is served, but must comply with existing service standards or set by the institution as a service provider with full commitment and readiness to solve problems that arise in a professional way. The purpose of this study is to identify the strategy for implementing excellent service in PT Jamun Medical Indonesian Majalaya branch, Bandung Regency. The research method applied here is qualitative descriptive analysis, which is an approach used to collect data and describe real events based on phenomena faced in society, with the hope that the research object can be presented in detail. After the research, the researcher can conclude that the excellent service at PT Jamun Medical Indonesian Majalaya branch, Bandung Regency can be said to be not good due to several influencing factors.